1997
DOI: 10.1029/96rs03468
|View full text |Cite
|
Sign up to set email alerts
|

First results of tropospheric gravity wave momentum flux measurements over Christmas Island

Abstract: Abstract. The importance of gravity wave effe. cts on various dynamical processes has been well documented in the upper and middle atmosphere. However, less is known about these waves in the lower atmosphere. Whereas many studies of longer-period waves have previously been conducted using wind profiler data, this paper is an effort to quantify the short-term motions of the troposphere. We will present some of the initial tropospheric gravity wave horizontal variance and momentum flux estimates calculated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…It is noticed that the magnitude and pattern of the momentum flux value, in general, is comparable to the results of early radar and non-radar studies of vertical flux (Fukao et al, 1988;McAfee et al, 1989;Sato, 1989;Worthington et al, 1996;Alexander and Pfister, 1995;Chang et al, 1997). In general, the momentum flux pattern and its general characteristics observed in the present work are similar to that of the observations mentioned above.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It is noticed that the magnitude and pattern of the momentum flux value, in general, is comparable to the results of early radar and non-radar studies of vertical flux (Fukao et al, 1988;McAfee et al, 1989;Sato, 1989;Worthington et al, 1996;Alexander and Pfister, 1995;Chang et al, 1997). In general, the momentum flux pattern and its general characteristics observed in the present work are similar to that of the observations mentioned above.…”
Section: Resultssupporting
confidence: 91%
“…Alexander and Pfister (1995) have shown that gravity waves propagate away from deep convection. The effect of the transfer of momentum from one region of the atmosphere to another can be seen from the changes in the mean flow acceleration (Chang et al, 1997). Fritts et al (1990) calculated vertical fluxes of zonal momentum per unit mass as −0.1 m 2 s −2 to 0.1 m 2 s −2 and found that near the tropopause jet, it is associated with a net acceleration of approximately 1-2 ms −1 d −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexander and Pfister (1995) studied the vertical flux of horizontal momentum carried by short horizontal scale gravity waves (λ x =10-100 km) using aircraft measured winds in the lower stratosphere. Chang et al (1997) used ST radar data from Christmas Island to study tropospheric gravity waves, and they found a broad range of frequency associated with gravity wave activity in the troposphere. The derived flux values agree well with the values obtained from MU radar and by Rao et al (1997), Dhaka et al (2001).…”
Section: V Subba Reddy Et Al: Studies On Atmospheric Gravity Wavmentioning
confidence: 99%
“…Owing to smaller temporal and spatial scale sizes of cumulus convection, its observations at meso-scale using existing techniques like rockets and satellites have been extremely difficult. Significant improvements in the MST radar technique have led to study these wave phenomena with large spatial and temporal resolutions (Balsley and Gage, 1980;Worthington and Thomas, 1997;Chang et al, 1997). VHF radar is a promising tool to study such events and their dynamical effects, because MST radars offer the unique capability of directly measuring the vertical velocity and also horizontal velocities with high spatial and temporal resolutions.…”
Section: Introductionmentioning
confidence: 99%